Effect of Aloe vera Gel Administrated on Reproductive Performance of Female Rats - Gunawan G; Enny T Setiatin; Bayu Rosadi; Thomas Mata Hine; A. Parakkasi (Jurnal Kedokteran Hewan, 2007)
The research was conducted to find out the effect of Aloe vera gel administrated orally onreproductive performance of female rats. Fifteen two months old female rats were alloted to fivetreatments of per oral Aloe vera gel administration: P0 (control), P1(1 mg /g body weight), P2 (2 mg/gbody weight, P3 (3 mg/g body weight), and P4 ( 4 mg/g body weight). The gel were administrated everyday for four weeks. The body weight were measured on the same day as last treatment. The animal thenmated to proven male on 1:1 rasio. Positively mated animals were sacrificed on D-10 after mating tocollect uterus and ovary so the number of fetus, corpus luteum, and ovary weight can be determined. Thetreatments significantly decreased (P0.05) the average body weight gain. The P0 (4.1 g/head/day) wasdifferent to P1 (2.69 g/head/day), P2 (2.87 g/head/day, and P4 (2.68 g/head/day), but was not different toP3 (3.39 g/head/day). The ovarium weight were not different (P0.05) among the treatments, so did thenumber of corpus luteum (CL), the number of fetuses and the CL: fetus rasio.Keywords: Aloe vera, rats, reproductive performance .